Learning Organisation and Readiness for Change in Higher Education Institutions: The Intervening Role of Organizational and Individual Resilience - AL-QUQA, ENASS K. I. (2024)
Higher education institutions today face an increasingly complex and rapidly changing environment. To adapt and respond effectively, they must develop themselves as learning organizations that foster readiness for change. Developing resilience is critical at both levels the individual and organizational to this process, as it empowers higher education institutions to navigate through challenges effectively. However, research on the interrelationships between these constructs in higher education institutions is limited. Understanding these potential links is crucial for higher education institutions seeking to enhance their change readiness capabilities. Against this background, this thesis examines the mediating role of individual and organizational resilience on the relationship between learning organization and readiness for change in higher education institutions in the United Arab Emirates (UAE). A learning organization is an organization that encourages and facilitates continuous learning and development among its members to adapt and thrive in a rapidly changing environment. Its conceptual framework, rooted in the literature review, employs a model elucidating the interplay between a learning organization and organizational readiness, mediated by individual and organizational resilience. It relies on learning organization theory, readiness for change theory, and resilience theory to elucidate this process. The model is tested with a sample of 404 respondents collected from four higher education institutions in the UAE. Here, a quantitative approach using partial least squares structural equation modeling (WarpPLS-8.0 version) is employed. The results indicate that individual and organizational resilience mediate the positive relationship between learning organization and readiness for change. Specifically, learning organization has a strong positive effect on individual and organizational resilience, and both types of resilience positively affect readiness for change. However, the data indicates that, compared to organizational resilience, individual resilience has a stronger mediating impact on individual readiness for change. On the other hand, the results indicate that organizational resilience has a stronger mediating impact on organizational readiness for change. Moreover, the findings confirm that resilience at the individual and organizational levels is crucial for translating learning organization practices into improved readiness for change within higher education institutions. As learning organizations, UAE universities can enhance change readiness by deliberately building resilience capacities in their workforces. The thesis contributes to the literature by investigating the three key concepts and applying the model specifically in UAE higher education institutions. The findings have practical implications for UAE universities seeking to enhance their adaptability and responsiveness to change. As learning organizations, they can build resilience capacities among faculty and staff to strengthen organizational change readiness. Fostering individual resilience is critical, as this study shows it plays a more significant role in mediating the link between learning organization practices and readiness for change.